PIV and dynamic LES of the turbulent stream and mixing induced by a V-grooved blade axial agitator - González-Neria, Israel; Alonzo-Garcia, Alejandro; Martínez-Delgadillo, Sergio A.; Mendoza-Escamilla, Víctor X.; Yáñez-Varela, Juan Antonio; Verdin, Patrick G.; Rivadeneyra-Romero, Gabriela (Elsevier, 2019)
The hydrodynamic behavior of a turbulent flow and the mixing characteristics generated by a V-grooved axial impeller inside an agitated tank reactor were investigated both experimentally and numerically. Angle resolved Particle Image Velocimetry (PIV) techniques with an angular displacement Δθ = 5° have been applied and two aerodynamic planes along the blades were considered. PIV-based results were compared to those obtained by Large Eddy Simulation (LES), used with the dynamic Smagorinsky-Lilly sub-grid scale (SGS) model. Results showed the existence of distinctive recirculation zones in the aerodynamic planes, and new additional frequencies in the impeller stream, induced by the grooves. A decrease of mixing time of about 11% was obtained experimentally, consequence of the better suction induced by the grooved blades in the early stages of mixing. Mean velocities, vorticity, TKE obtained from LES showed a good agreement with the PIV-based results. The distributions of turbulence dissipation rate ε were similar to those obtained from PIV, however showing high under-predicted magnitudes.
Keywords: V-grooves; PIV; LES; Turbulent flow; Dissipation rate; Axial impeller